Improving Substance Use Treatment for First Nations, Métis and Inuit Women: Recommendations Arising From a Virtual Inquiry project - Poole, Nancy; Chansonneuve, Deborah; Hache, Arlene (First Peoples Child & Family Review, 2013)
This article describes the work undertaken by participants in a virtual community, who came together online over a 15-month period to improve supports for First Nations, Métis and Inuit women with substance use problems at risk of having a child affected by Fetal Alcohol Spectrum Disorder (FASD). The project exemplifies a collaborative process, inclusive of people from various geographical locations, cultures and professional sectors, affording participants the opportunity to weave together research, practice wisdom, policy expertise, and Indigenous Knowledge(s) in a voluntary, nonhierarchical context. Such virtual processes have the potential to support the development of nuanced recommendations reflective of the complexities of FASD prevention in Indigenous contexts taking into account multiple influences on women’s substance use, and a continuum of treatment responses. The article includes participants’ recommendations for improving Canada’s substance use system of care to address the treatment and support needs of First Nations, Métis and Inuit women.